MOTIVASI PESERTA DIDIK SMPN 3 SEKADAU HULU DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI DAN OLAHRAGA - Suherdi Anderias; Eka Supriatna; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aimed to know the size of students' motivation in SMPN 3 Sekadau Hulu in teaching learning sports program. The method of this research was descriptive research in research survey form The, population.’ of this research were the students of SMPN 3 Sekadau  Hulu that have 6 classes with 210 Students. The sampling technique was used in this research was simple random sampling that have 110 students. To collect the data the researcher was used direction observational technique. The instrument  used was questionnaires. Based on the data collected, the students motivation of SMPN 3 Sekadau Hulu in teaching learning sports subject in all results by all indicators that have been collected from the students answers from 33  of 110 students was in highest category with 26 students (23.64%), high 53 Students  (48.18%),  low 26 students ( 23.63% ) and lowest with 5 students ( 4.55%).Keywords: Motivation of student physical education and sports.